The impact of healthcare workers' job stress caused by COVID-19 on travel intention and willingness to pay. Issue 2 (3rd April 2023) - Durgun, Sait; Tayfun, Ahmet
ABSTRACT: This study aims to examine the impact of healthcare workers' job stress (JS) from fear of COVID-19 (FC) on travel intentions (TI) and willingness to pay (WTP). It also investigates the direct path between FC and WTP. Moreover, it tests the moderation role of FC on the relationship between healthcare workers' JS and TI. Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed to analyze the data gathered from 401 frontline registered nurses working in pandemic hospitals in Turkey. The findings revealed that healthcare workers have the intention to travel and are willing to pay more for additional safety measures. The findings also indicated that FC negatively moderates the link between JS and TI. The results of this study provide theoretical and practical implications for tourism practitioners and marketers.